The many‐faced Janus of plant breeding. Issue 4 (4th March 2019) - Kantar, Michael B.; Runck, Bryan C.; Raghavan, Barath; Joglekar, Alison B.; Senay, Senait; Krohn, Brian; Neyhart, Jeffrey; Bradeen, James; Soto Gomez, Marybel; Kjelgren, Roger
Societal Impact Statement : Plant breeding is crucial for improving agricultural crops for human use. However, an urgent rethink is needed to ensure the next generation of plant breeders have the necessary breadth of skills to provide ever more efficient, nutritious, profitable, and environmentally sustainable crops. Plant breeding is a multifaceted endeavor, which intersects with many other disciplines and professions. To help ensure that future plant breeding efforts are sustainable and relevant to the needs of society, it is vital that the interdisciplinary nature of the plant breeding profession is adequately reflected in student training and development. Summary Breeders need to have many faces to understand not only genetics but also environmental, social, and economic factors that are relevant for maintaining or improving crops for human use. In the United States, there is a long history of public involvement in agriculture and plant breeding. However, recent changes in the social systems underpinning public agriculture (i.e., funding structure) necessitate a rethinking of how agriculture education, specifically plant breeding education, should be facilitated. To provide viable plant breeding programs, it is necessary to explicitly acknowledge that breeding has been an interdisciplinary, long‐standing public endeavor to increase food system stability. Acknowledging this complexity has important pedagogical implications: the core of plant breeding resides in genetics, but the changing nature of this profession requires breeders to embrace a much broader training. Here, we suggest specific curricular objectives for plant breeders. Abstract : Plant breeding is crucial for improving agricultural crops for human use. However, an urgent rethink is needed to ensure the next generation of plant breeders have the necessary breadth of skills to provide ever more efficient, nutritious, profitable, and environmentally sustainable crops. Plant breeding is a multifaceted endeavor, which intersects with many other disciplines and professions. To help ensure that future plant breeding efforts are sustainable and relevant to the needs of society, it is vital that the interdisciplinary nature of the plant breeding profession is adequately reflected in student training and development.